The Effect of Network Solvation on the Viscoelastic Response of Polymer Hydrogels - Zidek, Jan; Kulovana, Eva; Jancar, Josef (Polymers, 2017)
The majority of investigations consider the deformation response of hydrogels, fully controlled by the deformation behavior of their polymer network, neglecting the contribution caused by the presence of water. Here, we use molecular dynamics simulation in an attempt to include the effect of physically bound water via polymer chain solvation on the viscoelastic response of hydrogels. Our model allows us to control the solvation of chains as an independent variable. The solvation of the chain is independent of other factors, mainly the effect (pH) which interferes significantly in experiments. The solvation of hydrophilic chains was controlled by setting a partial charge on the chains and quantified by the Bjerrum length (BL). The BL was calculated from the partial electric charge of the solvent and macromolecular network. When the BL is short, the repulsive Van der Waals interactions are predominant in the vicinity of macromolecules and solvation is not observed. For a long BL, the water molecules in the solvation zone of network are in the same range as attractive intermolecular forces and the solvation occurs. The model also allows the consideration of molecules of water attached to two chains simultaneously, forming a temporary bridging. By elucidating the relations between solvation of the network and structural changes during the network deformation, one may predict the viscoelastic properties of hydrogels knowing the molecular structure of its polymer chains.
Keywords: molecular dynamics; hydrogel; deformation; solvation; water